Resource recovery from anaerobically digested liquor of wastewater screenings - Newati Wid; Nigel Horan (Universiti Malaysia Sabah, 2014)
Phosphorus is a limited resource which is predicted to be exhausted at some point during the 21st century. However, it is present in wastewaters at concentrations that come close to supplying the nation’s annual requirements for fertiliser. Therefore, this study was conducted to study the potential of wastewater screenings which has received little attention that produced during wastewater treatment, for phosphorus recovery. Many papers have addressed the recovery of phosphate or ammonia as struvite from different type of waste. The most prominent usage of struvite (magnesium ammonium phosphate hexahydrate) is as a slow-release fertiliser, suitable as replacement for chemical fertiliser, for agricultural application. In this study, digested liquor was obtained from anaerobically digested of wastewater screening. The experiments were carried out with and without chemical amendment to study the feasibility of phosphorus recovery, at different Mg:P molar ratio, i.e. 1.56:1 (without chemical amendment), 2:1 and 3:1 (with chemical amendments). Precipitation at 1.56:1 showed that phosphorus removal efficiency was 68% and recovered 0.52g amorphous calcium carbonate. Precipitation at 2:1 reduced phosphorus removal efficiency to 53% and the recovered solid was found to be calcium phosphate, with 0.33g precipitate. Precipitation at 3:1 was not economically interesting for P recovery as shown by its lowest removal efficiency and highest chemical usage. The results demonstrated that the presence of calcium and carbonate ion in the digested liquor highly interfere with phosphorus recovery in the form of struvite.